[OPy][BF4] Selective Extraction for Trace Hg2+ Detection by Electrochemistry: Enrichment, Release and Sensing - Chenyu Xiong; Yun Hui; Ri Wang; Chao Bian; Yuhao Xu; Yong Xie; Mingjie Han; Shanhong Xia (Micromachines, 2021)
Trace mercury ion (Hg<semantics>2+</semantics>) detection is important for environmental monitoring and water safety. In this work, we study the electrochemical strategy to detect trace Hg<semantics>2+</semantics> based on the preconcentration of temperature-controlled N-octylpyridinium tetrafluoroborate ([OPy][BF<semantics>4</semantics>]) dispersive liquid–liquid microextraction. The [OPy][BF<semantics>4</semantics>] selectively extracted Hg<semantics>2+</semantics> from aqueous solution by the adsorption of unsaturated N in [OPy][BF<semantics>4</semantics>], which increased the concentration of Hg<semantics>2+</semantics> and decreased that of other interference ions. It was noted that the adsorption of [OPy][BF<semantics>4</semantics>] to Hg<semantics>2+</semantics> was weakened by aqueous solution. Hence, after extraction, precipitated [OPy][BF<semantics>4</semantics>] was diluted by a buffer solution comprising a mixture of water and acetonitrile to release Hg<semantics>2+</semantics> and the single was detected by electrochemistry. Water is proposed to release Hg<semantics>2+</semantics> adsorbed by [OPy][BF<semantics>4</semantics>], and the acetonitrile serves as a co-solvent in buffer solution. Sensitivity and anti-inference ability of sensors were improved using the proposed method and Hg<semantics>2+</semantics> releasing procedure. The detection limit (S/N = 3) of the sensor is 0.0315 <semantics></semantics>μg/L with a linear range from 0.1 to 1 <semantics></semantics>μg/L. And the sensor exhibits good recovery with an range from 106 % to 118%, which has great potential for trace Hg<semantics>2+</semantics> determination.